A Feasibility Study of rice bran wax as an alternative wax in scented candle making - Alvarez, Aira Floreine L.; Aquino, Grace Angellie T.; Bronsburac, Kathleen D.; Castillo, Maryrose N.; Laguinlin, Alexis Carl V.; Ramilo, Bianca Marie O.; Resurreccion, Nicole L.; Reyes, Aina Rose C.; Santos, Lei Nicole N.; Yape, Noel B. 4 0 16; 5
EXECUTIVE SUMMARY: This section provides an overview of the proposed business and intends to give the readers a holistic understanding of the general plans of the proponents. Likewise, it highlights the key points and aspects necessary for establishing a business. In addition, the executive summary includes a rundown of market analysis, technical feasibility, management feasibility, financial feasibility, and socio-economic feasibility. Moreover, the executive summary outlines the business name, business logo, a brief description of the business, methods of financing, and long-run objectives. A. Business Name- La vie en Flames is the chosen proposed business name of the partnership which was derived from the debut song La vie en Rose of a Korean Pop Group, IZ*ONE. The hit single has been a trend in the country for so long especially for K-Pop fans as it portrays an energetic and tranquil beat. The name was chosen as the song title will make the business name easier to recognize by its market. Aside from this reason, the meaning behind La vie en Flames also summarizes the mission and vision of the business. La vie en means to love while Flames symbolizes the product that the business offer which is candles. By combining the meaning of the two, La vie en Flames goes by their tagline, to feel love is to embrace the light. The business name is perfect for a product that strives to stimulate more vision and meditation through candles. La vie en Flames owners want to convey to their customers that scented candles are one of the outlets they can use to feel refreshed and create a sense of tranquility and calmness when used to their potential. Overall, La vie en Flames scented candles are recommended to individuals who wanted to restore control of their lives or gain harmony with it.
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2